THE READINESS OF PLP 2 UKI TORAJA STUDENT TO BECOME A COMPETENT ENGLISH TEACHER: AN ANALYSIS OF THE FOUR TEACHER COMPETENCIES - Pasauran, Masriany; La'biran, Roni; Sallata, Yizrel Nani (Publikasi dan UKI Press UKI Toraja., 2024)
The objective of the research is to find out how is the level of readiness of PLP 2 UKI Toraja students to become competent English teachers based on the four teacher competencies. This research refers to the four standard teacher competencies, namely pedagogic competence, professional competence, personality competence, and social competence. In this study, researchers used quantitative research methods. The instrument used was a questionnaire in the form of a Likert scale. Data processing used descriptive percentage analysis, which is a description of the questionnaire consisting of 23 statement items. Answers from the questionnaire were obtained from 92 students from SMPN 1 Rantepao as respondents. Based on the results of this research, it was concluded that the readiness of PLP 2 UKI Toraja students to become competent English teachers was classified as very ready based on the four teacher competency standards. This can be seen from the achievement results of the data calculations obtained, it was found that the pedagogic competence of PLP 2 UKI Toraja students was 85.22%, professional competence obtained a percentage of 87.88%, personality competence with a percentage of 91.41%, and social competence which received an assessment from students with a percentage of 85.48%. The results of all these percentages fall into a very ready level of readiness with a range (71%-100%) to become a competent teacher candidate.